THE USE OF LEARNING STRATEGIES IN THE COURSE COMPUTING FOR STUDENTS IN SEVENTH GRADERS. - Álvarez Mesa. , Yuniesky; Cao González., Gilberto Vicente (Atenas, 2013)
The introduction of scientific and technological advances in education provides a source of improvement and development, while generating conflicts that hinder their efficient implementation. Schools are the center of this activity, which presupposes a reconceptualization of the educational process. The commitment to this work is given to pedagogical methodological recommendations to enhance the use of learning strategies in the course computing for students in seventh grade junior high and contribute to experimentation and design of active modes of interaction with the technologies computer at school.